2021
DOI: 10.1007/jhep06(2021)164
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of diligence: how precise are predicted gravitational wave spectra in models with phase transitions?

Abstract: Models of particle physics that feature phase transitions typically provide predictions for stochastic gravitational wave signals at future detectors and such predictions are used to delineate portions of the model parameter space that can be constrained. The question is: how precise are such predictions? Uncertainties enter in the calculation of the macroscopic thermal parameters and the dynamics of the phase transition itself. We calculate such uncertainties with increasing levels of sophistication in treati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 115 publications
(117 reference statements)
0
31
0
Order By: Relevance
“…The other quantities are introduced by using the relation H 2 = 8πGρ tot /3, assuming that the total energy density can be decomposed into vacuum and radiation energy densities, ρ tot = ρ vac +ρ rad , and assuming that the vacuum energy density coincides with the latent heat released at the phase transition. These approximations can be improved (see [136,137] for recent discussions), but are useful to focus on the calculation of the dimensionless quantity ∆ for a simplified phase transition kinematics and then applying Eq. ( 10) to specific realistic models (see, e.g., [93,114]).…”
Section: Dimensionless Gw Spectrummentioning
confidence: 99%
“…The other quantities are introduced by using the relation H 2 = 8πGρ tot /3, assuming that the total energy density can be decomposed into vacuum and radiation energy densities, ρ tot = ρ vac +ρ rad , and assuming that the vacuum energy density coincides with the latent heat released at the phase transition. These approximations can be improved (see [136,137] for recent discussions), but are useful to focus on the calculation of the dimensionless quantity ∆ for a simplified phase transition kinematics and then applying Eq. ( 10) to specific realistic models (see, e.g., [93,114]).…”
Section: Dimensionless Gw Spectrummentioning
confidence: 99%
“…[9] we employ the optimistic estimate turb 10 %. An accurate prediction of the spectrum of GWs generated in a first-order phase transition in the early universe for a given model can be very challenging, requiring numerical methods for the calculation of the effective potential, for the onset and duration of the phase transition, as well as for a description of bubble walls [46]. The focus of the present work is however not on the detailed dynamics of the phase transition itself, but on the cosmological evolution of the dark sector that gives rise to such a phase transition subsequent to the generation of a GW signal.…”
Section: Gravitational Waves From a Dark First-order Phase Transitionmentioning
confidence: 99%
“…A general review of more refined computational approaches than the one used in this work can be found in Ref. [46]. Most importantly, we used the nucleation temperature as a reference scale to define thermodynamic quantities.…”
Section: Gravitational Waves From a Dark First-order Phase Transitionmentioning
confidence: 99%
“…See also Ref [111]. where the magnitude of various uncertainties due to macroscopic, rather than quantum field theoretic, physics were investigated.…”
mentioning
confidence: 99%
“…While certainly important, none of these are quite as severe as those we find here. Our approach to the macroscopic physics can be described as moderately diligent in the language of Ref [111]…”
mentioning
confidence: 99%